2021
DOI: 10.1037/fam0000663
|View full text |Cite
|
Sign up to set email alerts
|

Cultural socialization in childhood: Analysis of parent–child conversations with a direct observation measure.

Abstract: Cultural factors influence the development of all children. Yet, current knowledge of explicit cultural socialization processes in childhood remains limited, mainly by failing to incorporate the experiences of young children. To address this critical gap, the authors introduce the OMERS-Peds task, an observational measurement designed to systematically identify and compare the content of cultural messages passed down from caregivers to offspring during early school age years. The OMERS-Peds was administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…First, according to Brown et al (2007), parents reported more frequent discussions about race with girls than with boys. Second, consistent with research on parents of color's ERS (Aguayo et al, 2021), eight studies documented that parents consider the child's age when deciding whether to engage in explicit ERS (Abaied and Perry, 2021;Aguayo et al, 2021;Barner, 2016;Bartoli, et al, 2016;Gillen-O'Neel et al, 2021;Pinsoneault, 2015;Underhill, 2016Underhill, , 2018Vittrup, 2018). Despite evidence that children learn about race and perceive racial differences at a young age (Pahlke et al, 2012), many parents think that young children cannot understand race (Vittrup, 2018), race is not salient to young children (Aguayo et al, 2021;Pinsoneault, 2015), or discussions of race would be harmful to young children (Gillen-O'Neel et al, 2021;Underhill, 2016Underhill, , 2018.…”
Section: Child Factors Relating To Engagement In Erssupporting
confidence: 73%
See 3 more Smart Citations
“…First, according to Brown et al (2007), parents reported more frequent discussions about race with girls than with boys. Second, consistent with research on parents of color's ERS (Aguayo et al, 2021), eight studies documented that parents consider the child's age when deciding whether to engage in explicit ERS (Abaied and Perry, 2021;Aguayo et al, 2021;Barner, 2016;Bartoli, et al, 2016;Gillen-O'Neel et al, 2021;Pinsoneault, 2015;Underhill, 2016Underhill, , 2018Vittrup, 2018). Despite evidence that children learn about race and perceive racial differences at a young age (Pahlke et al, 2012), many parents think that young children cannot understand race (Vittrup, 2018), race is not salient to young children (Aguayo et al, 2021;Pinsoneault, 2015), or discussions of race would be harmful to young children (Gillen-O'Neel et al, 2021;Underhill, 2016Underhill, , 2018.…”
Section: Child Factors Relating To Engagement In Erssupporting
confidence: 73%
“…They prefer to socialize children when they are older, such as in their teenage years. Teenage children are more likely than younger children to raise explicit questions about ethnicity–race ( Bartoli et al, 2016 ; Aguayo et al, 2021 ), enabling parents to perceive they are ready for ERS. Third, children’s inquiries about ethnicity–race prompt some parents to engage in ERS ( Gillen-O’Neel et al, 2021 ; Vittrup, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present set of articles is precisely concerned with these proximal microcontexts, what takes place within them, how they inform and condition theoretical propositions, and how their study can further a richer and more comprehensive understanding of family life. Several articles make creative use of structured or naturalistic video or audio recordings to capture cultural messaging (Aguayo et al, 2021), expressed positive emotion in naturalistic contexts (McNeil & Repetti, 2021), reliable assessment of behavior and affect from preschool children in the home (Micheletti et al, 2020), conversational exchanges between couples (Timmons et al, 2021), and sequences of solicitation and disclosure between adolescent and parent (Mounts & Valentiner, 2021). Another made use of observation and self-reports to classify triadic (mother–father–child) social networks within families (Heshmati, Blackard, Beckmann, & Chipidza, 2020).…”
Section: Calling For Dynamic Conceptualizations Of Contextmentioning
confidence: 99%